Jenis Hasil Tangkapan Menggunakan Alat Tangkap Purse Seine Di Pelabuhan Perikanan Namosain, Kupang - Sitanggang, Wanri (Program Studi Teknologi Hasil Perikanan - Universitas Kristen Wira Wacana Sumba, 2024)
The diversity of biological resources in Indonesian waters is relatively abundant. This abundance can be exploited without exceeding the fishing threshold, especially in Kupang waters. Catch limits in Kupang waters may change from time to time and can be regulated by local fisheries authorities. Local or national fisheries authorities set rules regarding the types of fish that can be caught, the minimum size of fish that can be caught, fishing seasons, and permitted fishing gear. KM. SEHATI 05 is one of the fishing vessels at the Namosain fishing port. This ship measures 16 GT and this ship uses purse seine fishing gear. Diverse and abundant catches of course require the operation of environmentally friendly fishing gear, for example purse seines. The catch targets for this tagfish are tuna, squid, trevally and barracuda. This can be seen based on the mesh size of the fishing gear. The aim of this research is to find out the types of catches that exist in KM. SEHATI 05 in the Namosain fishery using tools. The method used in this research is observation of catches and interviews with fishermen using Purse Seine fishing gear. The types of fish that are usually caught using Purse Seine fishing gear at KM SEHATI 05 are generally only a few types of pelagic fish such as squid (Loligo sp), barracuda fish (sphyraena), trevally fish (Atule mate), tembang fish (sardinella) fish. Tuna (Euthynnus affinis) catches are influenced by the size and shape of the fly, where the fishing gear used is a purse seine, where this fishing gear is made to catch pelagic fish. Keywords: Purse Seine, pelagic fish, aquatic resources and Kupang